MENENTUKAN KUALITAS RUBBER DENGA MENENTUKAN KUALITAS RUBBER DENGAN ALGORITMA NAÃVE BAYES: MENENTUKAN KUALITAS RUBBER DENGAN ALGORITMA NAÃVE BAYES - Muhammad Makmun Effendi (DPPM Universitas Pelita Bangsa, 2022)
In In the field of informatics engineering, theprediction of a special system to support decision making is a very influential factor in inputting assessment data and calculating values. With a Bayesian approach model in the form of applying the naive Bayes method in a decision support system to determine the quality of rubber. This method was chosen because it is a simple classification based on Bayesian application with assumptions between variables. The classification is divided into two stages, namely Learning (training) and testing, based on the test data obtained parameters such as type, temperature, hardness, density and elasticity, with the acquisition of OK or NG results based on calculations using the Naive Bayes method.